Upcycling – a new perspective on waste in social innovation - Wegener, Charlotte; Aakjær, Marie (Journal of Comparative Social Work, 2016)
The purpose of this paper is to introduce ‘upcycling’ – a well-known term within design practice – to the field of social innovation. A mix between ‘upgrading’ (adding value) and ‘recycling’ (reusing) creates the word upcycling, which, in its simplest terms, is the practice of reassessing waste and transforming it into something valuable. In this paper, we ask: How does an upcycle mind-set and practice contribute to situated social innovation? This conceptual paper seeks to combine insights from the fields of social innovation and co-design with the ideas inherent in upcycling. To ground the theorizing of what we term ‘social upcycling’, four cases are used to illustrate what upcycling practices look like. The cases illustrate the diversity of actors, activities and materiality involved in social upcycling processes. Concluding, the paper outlines a new promising area of social innovation and some practical implications.